The condition of poverty: a case study of low socioeconomic status on Chinese students' National College Entrance Exam and college enrolment. Issue 1 (2nd January 2019) - Liu, Dongfang; Ku, Heng-Yu; Morgan, Thomas Lee
ABSTRACT: The condition of poverty is pervasive worldwide and is multifaceted in its ability to have a deleterious generational impact. Although China has greatly reduced the proportion of people living in abject poverty over the past three decades, there are still millions of families living in extreme poverty. This study investigated the influences of families' socioeconomic status on students' educational achievement in China with regard to the National College Entrance Exam (NCEE) scores and subsequent college enrolment. We interviewed 132 recent high school graduates from schools in six urban cities from low-socio-economic status (SES) homes. The findings revealed that school climate (general school quality, student-teacher interactions, and peer pressure) and home environment (parental support, student-parent relationship, and family size) negatively impacted their educational achievement. Students were cognisant that the schools they attended did not have the same high reputation as schools attended by their more affluent peers and felt that their teachers openly discriminated against them. Additionally, their parents did not have the time or financial resources to help them advance educationally. We propose the low-SES Educational Achievement Framework to illustrate the phenomenon of environmental conditions that may influence the low-SES students' NCEE scores and ultimately result in low college enrollment rates in China.